Chemical Cutting of Perovskite Nanowires into Single‐Photon Emissive Low‐Aspect‐Ratio CsPbX3 (X=Cl, Br, I) Nanorods. Issue 49 (8th November 2018) - Tong, Yu; Fu, Ming; Bladt, Eva; Huang, He; Richter, Alexander F.; Wang, Kun; Müller‐Buschbaum, Peter; Bals, Sara; Tamarat, Philippe; Lounis, Brahim; Feldmann, Jochen; Polavarapu, Lakshminarayana
Abstract: Post‐synthetic shape‐transformation processes provide access to colloidal nanocrystal morphologies that are unattainable by direct synthetic routes. Herein, we report our finding about the ligand‐induced fragmentation of CsPbBr3 perovskite nanowires (NWs) into low aspect‐ratio CsPbX3 (X=Cl, Br and I) nanorods (NRs) during halide ion exchange reaction with PbX2 –ligand solution. The shape transformation of NWs‐to‐NRs resulted in an increase of photoluminescence efficiency owing to a decrease of nonradiative decay rates. Importantly, we found that the perovskite NRs exhibit single photon emission as revealed by photon antibunching measurements, while it is not detected in parent NWs. This work not only reports on the quantum light emission of low aspect ratio perovskite NRs, but also expands our current understanding of shape‐dependent optical properties of perovskite nanocrystals. Abstract : Quantum emitter : CsPbBr3 perovskite nanowires (NWs) break into low aspect‐ratio CsPbX3 (X=Cl, Br and I) nanorods (NRs) of different halide compositions by reaction with PbX2 –ligand solution. These perovskite NRs can serve as quantum light sources at room temperature, while the corresponding NWs did not show photon antibunching characteristics.